2015
DOI: 10.1634/theoncologist.2015-0234
|View full text |Cite
|
Sign up to set email alerts
|

Use of Palliative Care Services in a Tertiary Cancer Center

Abstract: This study analyzed palliative/supportive care use in a single cancer center over 8 years. Billing data showed the inpatient consultations as a percentage of hospital admissions and the ratio of inpatient consultations to hospital beds almost doubled. In the outpatient setting, data revealed earlier access to outpatient referrals to palliative care service (from 4.8 months to 7.9 months; p = .001) during the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Furthermore, they also reported that a larger proportion of their own patients with advanced cancer were referred to palliative care, with a gradient effect observed. Our findings are consistent with the observation that palliative oncologists who are dually trained in oncology and palliative care often refer a high proportion of their patients to palliative care when practicing oncology [18].This association could also help explain the steady growth of the palliative care program at our institution [6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, they also reported that a larger proportion of their own patients with advanced cancer were referred to palliative care, with a gradient effect observed. Our findings are consistent with the observation that palliative oncologists who are dually trained in oncology and palliative care often refer a high proportion of their patients to palliative care when practicing oncology [18].This association could also help explain the steady growth of the palliative care program at our institution [6].…”
Section: Discussionsupporting
confidence: 90%
“…This model of integrated, collaborative care has been shown to improve patient outcomes, including quality of life, symptom distress, illness understanding, satisfaction, and even survival [3,4]. Oncologists generally agree that palliative care delivery is one of their key responsibilities [5]; however, how much primary and secondary palliative care their patients actually receive is likely affected by many factors, such as local resource availability, patient preference, oncologist's palliative care training, and their attitudes toward end-of-life (EOL) care [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is staffed by 18 board‐certified palliative care physicians, together with palliative care‐trained registered nurses, pharmacists, social workers, counselors, and psychologists. It predominantly serves patients who have advanced cancer and also serves a relatively smaller number of patients who have early stage disease and early remission . The patient and his or her family are initially assessed by the nurse, who gathers pertinent clinical information.…”
Section: Methodsmentioning
confidence: 99%
“…Several centers have published their experience with freestanding outpatient clinics . In most cases, these clinics have begun as single, one‐half–day clinics per week and have grown quickly with increasing demand . Large cancer centers, such as The University of Texas MD Anderson Cancer Center and the Princess Margaret Cancer Center, have clinics that operate daily and offer both booked and urgent same‐day appointments.…”
Section: Innovative Models Of Care Deliverymentioning
confidence: 99%